2009
DOI: 10.1084/jem.20081922
|View full text |Cite
|
Sign up to set email alerts
|

CSL–MAML-dependent Notch1 signaling controls T lineage–specific IL-7Rα gene expression in early human thymopoiesis and leukemia

Abstract: Notch1 activation is essential for T-lineage specification of lymphomyeloid progenitors seeding the thymus. Progression along the T cell lineage further requires cooperative signaling provided by the interleukin 7 receptor (IL-7R), but the molecular mechanisms responsible for the dynamic and lineage-specific regulation of IL-7R during thymopoiesis are unknown. We show that active Notch1 binds to a conserved CSL-binding site in the human IL7R gene promoter and critically regulates IL7R transcription and IL-7R α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 44 publications
4
84
0
Order By: Relevance
“…A recent study suggests that in addition to maintaining the survival of developing lymphocytes, IL-7 signaling promotes the growth and proliferation of DN4 cells by increasing levels of trophic receptors, such as CD71 and the amino acid transporter CD98 (Pearson et al, 2012;Boudil et al, 2015), activities that were previously attributed mainly to Notch1 signaling. However, Notch1 can induce IL-7R expression and therefore its effects could be downstream of IL-7 signals (González-García et al, 2009;Magri et al, 2009).…”
Section: Activation and Effector T Cell Differentiationmentioning
confidence: 99%
“…A recent study suggests that in addition to maintaining the survival of developing lymphocytes, IL-7 signaling promotes the growth and proliferation of DN4 cells by increasing levels of trophic receptors, such as CD71 and the amino acid transporter CD98 (Pearson et al, 2012;Boudil et al, 2015), activities that were previously attributed mainly to Notch1 signaling. However, Notch1 can induce IL-7R expression and therefore its effects could be downstream of IL-7 signals (González-García et al, 2009;Magri et al, 2009).…”
Section: Activation and Effector T Cell Differentiationmentioning
confidence: 99%
“…Moreover, since the inhibition of Akt was without effect on Lmx1a activity (Figure 3 ) we believe that the effect of PI3K is independent of Akt. There are reports that signal crosstalk downstream of VEGF and EGF receptors occurs between PI3K [21,44] and Notch [45] within multiple tissue systems [4648] and can occur both dependent and independent of Akt [49]. As this is the first report of DNA-PK involvement in neural specification, the neurogenic potential of cultures following the inhibition of DNA-PK was also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IL7R gain-of-functions mutations [106,107] serve as an alternative route for enhanced PI3K/AKT/mTOR signaling in leukemic T-cells. Finally, aberrant NOTCH1 signaling will further enhance PI3K/AKT/mTOR activation through NOTCH1-mediated transcriptional upregulation of the IL7R [113] and HES1-mediated transcriptional repression of PTEN [123]. Notably, in some T-ALL cases, loss of PTEN can occur during disease progression and switch the oncogene addiction from NOTCH1 towards constitutive AKT signaling [123].…”
Section: The Pi3k-akt-mtor Pathwaymentioning
confidence: 95%
“…This genetic evidence combined with the transcriptional regulation of IL7R by activated NOTCH signaling [113] and/or sustained ZEB2 activity [54], marks this signaling axis as a highly attractive target for molecular therapy and therefore provides a strong rational for the use of clinical-stage JAK-or STAT-specific small molecule inhibitors in a significant fraction of human T-ALL patients (Figure 2). Indeed, Goossens and colleagues demonstrated that increased IL7R in Zeb2 driven immature T-ALL is associated with increased cell survival and secondary leukemia initiating potential upon xenotransplantation, which could be perturbed by administration of an IL7R blocking antibody [48].…”
Section: The Il7r-jak-stat Pathway As a Therapeutic Targetmentioning
confidence: 96%